Knot-tack Sewing / Knotenheftung – Its Possible Origin and Identification in Today's Upper Austria. Issue 1 (2nd October 2021) - Ehrl CanReg, H. Harald; Engel, Patricia; Schuster OSB, Petrus
ABSTRACT: Knot-tack sewing was discovered in Austrian libraries in the 1940s and this finding was published by Eleonore Klee. Her communication with Christopher Clarkson thereafter is published in the contribution for the first time. Furthermore, E. Klee's observations going beyond her published texts and traced by revisiting the relevant codices in the Abbeys of Kremsmünster and St. Florian are described. These observations lead to the suggestion that the knot-tack sewing was invented about 100 years earlier than so far believed.